Pelatihan Penyusunan Bahan Ajar dan Asesmen Interaktif Bermuatan Kearifan Lokal Melalui AI Untuk Meningkatkan Literasi Digital Guru SD - Setiawaty, Rani; Najikhah, Fatikhatun; Agung Santoso, Denni; Amaliyah, Fitriyah (Universitas Nusantara PGRI Kediri, 2025)
The transformation of 21st-century education requires teachers to not only master the subject matter but also be able to utilize digital technology in developing teaching materials and assessments that are relevant to the local context. This community service program aims to enhance the competencies of elementary school teachers in Bacin Village, Kudus District, in creating interactive teaching materials and assessments based on local wisdom literacy with the assistance of Artificial Intelligence (AI) technology. The activities were conducted offline using a participatory-collaborative approach through several stages: needs identification, training, mentoring, and evaluation. The training materials covered the use of AI platforms such as ChatGPT, Gamma AI, Canva AI, and Educaplay to develop interactive teaching materials and quizzes that highlight local cultural values such as Gusjigang, historical buildings, and Kudus's signature cuisine. The training results showed a significant improvement in teachers' understanding of local literacy and digital literacy concepts related to AI technology use. The average improvement in understanding reached 80%. The products produced include simple teaching materials (e-modules and handouts) and digital assessments (Educaplay). Additionally, survey results indicate that 100% of participants recognize the importance of integrating local cultural values into learning. This training demonstrates that the integration of AI and local wisdom can empower teachers to become adaptive and contextual learning facilitators.